High-performance non-stick pan coating and preparation process thereof
A high-performance non-stick pan coating with a specific composition and preparation process addresses the issues of scratch resistance and adhesion, enhancing durability and longevity by forming a compact network structure.
Patent Information
- Application Number
- CN202411500543.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-25
AI Technical Summary
Traditional non-stick pans have coatings that are easily scratched and damaged, leading to reduced non-stick performance due to their softness and vulnerability to metal spatulas, and they are difficult to clean when food sticks to the pot bottom.
A high-performance non-stick pan coating composed of bisphenol A epoxy resin, propanol, zirconium phosphate layered nanoparticles, nano silicon nitride, modified graphene, nano silicon dioxide, leveling agent, and silane coupling agent, with a specific preparation process involving mixing, ultrasonic treatment, and sintering to form a compact network structure.
The coating exhibits enhanced heat resistance, corrosion resistance, hardness, and wear resistance, forming a firm bond with the metal substrate, reducing scratches and improving adhesion, cohesion, and extending the cookware's service life.
Smart Images

Figure BDA0005102471280000071 
Figure BDA0005102471280000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a high-performance non-stick pan coating and a preparation process thereof. Background Art
[0002] Cookware is commonly used in daily life. According to their functions, they are divided into pressure cookers, frying pans, woks, soup pots, steamers, milk pots, rice cookers, etc.; according to their materials, they are divided into stainless steel pots, iron pots, aluminum pots, casseroles, copper pots, enamel pots, composite material pots, etc.; according to the number of handles, they are divided into single-ear pots and double-ear pots; according to the shape of the bottom of the pot, they are divided into flat pans and round-bottomed pots, etc. In the process of daily cooking or cooking, if the fire is high and the pot body is heated, the food often sticks to the bottom of the pot and often burns. In addition, the food adhered to the pot has a strong adhesion and is difficult to clean. With the development of productivity, the advent of non-stick pans has brought great convenience to people's lives. However, the coating of traditional non-stick pans is relatively soft, and users sometimes use metal spatulas when cooking. Due to the high hardness of the product, after long-term use, the coating in the pot is often scratched and damaged, which in turn affects its non-stick effect. Summary of the invention
[0003] In view of this, the present invention proposes a high-performance non-stick pan coating and a preparation process thereof to solve the above problems.
[0004] The technical solution of the present invention is achieved as follows: a high-performance non-stick pan coating comprises the following raw materials in parts by weight: 10-24 parts of bisphenol A epoxy resin, 12-36 parts of propanol, 6-12 parts of surfactant, 20-40 parts of zirconium phosphate layered nanoparticles, 4-8 parts of nano silicon nitride, 6-8 parts of nano silicon dioxide, 4-16 parts of modified graphene, 1-3 parts of leveling agent, and 1-3 parts of silane coupling agent.
[0005] Furthermore, a high-performance non-stick pan coating includes the following raw materials in parts by weight: 16 parts of bisphenol A epoxy resin, 24 parts of propanol, 9 parts of surfactant, 30 parts of zirconium phosphate layered nanoparticles, 6 parts of nano silicon nitride, 7 parts of nano silicon dioxide, 10 parts of modified graphene, 2 parts of leveling agent, and 2 parts of silane coupling agent.
[0006] Further, the modified graphene is prepared by the following method: adding graphene powder to anhydrous ethanol at 20-30°C, stirring at 300-500rpm for 10-20min to prepare a graphene ethanol dispersion, wherein the mass volume ratio of the graphene powder to the anhydrous ethanol is (0.03-0.05):(3.0-4.0) g / mL; stirring the hydroxyl-terminated polyamide and zinc dioxide at 300-500rpm for 5-10min, and adding them dropwise to the graphene ethanol dispersion, wherein the mass volume ratio of the hydroxyl-terminated polyamide, zinc dioxide, and graphene ethanol dispersion is (0.04-0.10):(0.04-0. 10):(1.0-3.0), placing the above mixed solution in an ultrasonic device, ultrasonically treating it for 25-35 minutes under the conditions of ultrasonic frequency of 20-40kHz and ultrasonic power of 100-300W, after the ultrasonic treatment, continuing to stir the mixed solution at 300-500rpm until a sol state is formed, placing the sol in a drying oven and drying it at 60-80°C for 6-10h to obtain a gel-like composite; placing the gel-like composite in a sintering furnace, sintering it at 200-400°C in an inert atmosphere for 40-60min; after the sintering, taking out the composite and cooling it to 20-30°C, grinding it to 30-50nm, and modifying the graphene.
[0007] Furthermore, the surfactant is one or a combination of polyvinyl alcohol, polyoxyethylene lauryl ether, sodium lauroamphoacetate, dodecyl dimethyl betaine, and potassium dodecyl phosphate.
[0008] Furthermore, the leveling agent is one of polydimethylsiloxane, octylphenol polyoxyethylene ether, and butyl acetate.
[0009] Furthermore, the silane coupling agent is one or a combination of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, and vinyltrimethoxysilane.
[0010] Furthermore, a preparation process of a high-performance non-stick pan coating comprises the following steps:
[0011] (1) adding bisphenol A epoxy resin, surfactant and zirconium phosphate layered nanoparticles into propanol, mixing and stirring under heating conditions of 40-50° C. to prepare a matrix solution;
[0012] (2) adding nano silicon nitride and nano silicon dioxide to the matrix solution, stirring evenly with ultrasonic waves, to obtain a mixed solution;
[0013] (3) Adding the graphene composite to the mixed solution, mixing evenly, and then adding a leveling agent and a silane coupling agent, mixing evenly, to obtain a high-performance non-stick pan coating.
[0014] Furthermore, in step (1), the stirring speed is 500-800 rpm, and the stirring time is 30-40 min. In step (2), the ultrasonic stirring power is 200-400 W, the ultrasonic frequency is 20-40 kHz, and the ultrasonic stirring time is 20-30 min. In step (3), when adding the graphene composite, stirring is performed at 300-500 rpm for 15-20 min, and when adding the leveling agent and the silane coupling agent, stirring is performed at 300-500 rpm for 10-15 min.
[0015] Furthermore, the high-performance non-stick pan coating is applied to the inner surface of the pan.
[0016] Compared with the prior art, the invention has the following beneficial effects: when the zirconium phosphate layered nanoparticles are uniformly dispersed in the coating, the heat-resistant temperature of the coating and the ability to resist corrosion by various chemical substances can be effectively improved, and the hardness, wear resistance and scratch resistance of the coating can also be significantly increased. At the same time, the active sites of the zirconium phosphate layered nanoparticles can form chemical bonds with the functional groups in the bisphenol A epoxy resin molecules, and the epoxy resin molecules are firmly fixed on the surface of the zirconium phosphate layered nanoparticles. Since the zirconium phosphate layered nanoparticles have a large specific surface area and a layered structure, a wide network structure can be formed in the coating, and this network structure closely connects the epoxy resin molecules with nano silicon nitride, nano silicon dioxide, a leveling agent and a silane coupling agent to form a more compact network structure, which helps to improve the adhesion, cohesion and overall mechanical properties of the coating, so that the coating is more firmly attached to the metal substrate and is not easy to fall off. In addition, during the coating curing process, the zirconium phosphate layered nanoparticles can be peeled off and arranged in a highly ordered manner to form a regular sheet structure. This orderly arrangement not only enhances the physical strength of the coating, but also forms an effective barrier that can greatly slow down or prevent corrosive media such as water, oxygen, acidic or alkaline substances from penetrating into the metal substrate, thereby significantly improving the anti-corrosion performance of the coating and extending the service life of the cookware.
[0017] In the present invention, terminal hydroxyl amide and zinc dioxide are used to modify graphene. The addition of terminal hydroxyl polyamide allows its amino functional group to interact with the graphene surface, and the amino functional group is introduced on the graphene surface by chemical bonding, which significantly enhances the compatibility of the modified graphene with epoxy resin. The amino functional group of the modified graphene reacts with the epoxy group and carboxyl group in the epoxy resin, promoting the cross-linking reaction between the components of the coating, thereby forming a more compact and firm coating structure. In the modified sol-gel transition and sintering process, zinc dioxide particles are attached to the graphene surface to form a composite reinforcement structure, which helps to improve the hardness and wear resistance of the modified graphene, so that it exhibits more excellent mechanical properties in non-stick pan coatings.
[0018] The surfactant in the present invention can be adsorbed on the surface of the zirconium phosphate layered nanoparticles, and is compatible with the epoxy resin matrix through its lipophilic group, while the hydrophilic group faces the outside of the particles to form a coating film. This coating film effectively reduces the surface tension between the nanoparticles, prevents the agglomeration of the particles, thereby improving the dispersion and orientation of the zirconium phosphate layered nanoparticles in the epoxy resin, so that the layered nanoparticles can efficiently exert their barrier effect, further improving the anti-corrosion performance of the coating. DETAILED DESCRIPTION
[0019] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.
[0020] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0021] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0022] Example 1
[0023] A high-performance non-stick pan coating includes the following raw materials in parts by weight: 10 parts of bisphenol A epoxy resin, 12 parts of propanol, 6 parts of surfactant, 20 parts of zirconium phosphate layered nanoparticles, 4 parts of nano silicon nitride, 6 parts of nano silicon dioxide, 4 parts of modified graphene, 1 part of leveling agent, and 1 part of silane coupling agent. Among them, the surfactant is polyvinyl alcohol, the leveling agent is polydimethylsiloxane, and the silane coupling agent is γ-glycidyloxypropyltrimethoxysilane. The modified graphene is prepared by the following method: adding graphene powder to anhydrous ethanol at 20°C, stirring at 300rpm for 20min to prepare a graphene ethanol dispersion, wherein the mass volume ratio of the graphene powder to the anhydrous ethanol is 0.03:3.0 g / mL; stirring hydroxyl-terminated polyamide and zinc dioxide at 300rpm for 10min, and adding them dropwise to the graphene ethanol dispersion, wherein the mass volume ratio of the hydroxyl-terminated polyamide, zinc dioxide, and graphene ethanol dispersion is 0.04:0.04 g / mL: 1.0, placing the above mixed solution in an ultrasonic device, and ultrasonically treating it for 35 minutes under the conditions of ultrasonic frequency of 20 kHz and ultrasonic power of 100 W. After the ultrasonic treatment, continue to stir the mixed solution at 300 rpm until a sol state is formed, and place the sol in a drying oven and dry it at 60° C. for 10 hours to obtain a gel-like composite; placing the gel-like composite in a sintering furnace, and sintering it at 200° C. for 60 minutes under an inert atmosphere; after the sintering, take out the composite and cool it to 20° C., grind it to 30 nm, and modify the graphene.
[0024] Example 2
[0025] A high-performance non-stick pan coating includes the following raw materials in parts by weight: 24 parts of bisphenol A epoxy resin, 36 parts of propanol, 12 parts of surfactant, 40 parts of zirconium phosphate layered nanoparticles, 8 parts of nano silicon nitride, 8 parts of nano silicon dioxide, 16 parts of modified graphene, 3 parts of leveling agent, and 3 parts of silane coupling agent. Among them, the surfactant is a 1:1 combination of polyoxyethylene dodecyl ether and sodium lauroylamphoacetate, the leveling agent is octylphenol polyoxyethylene ether, and the silane coupling agent is a 1:1 combination of γ-aminopropyl triethoxysilane and γ-methacryloxypropyl trimethoxysilane. The modified graphene is prepared by the following method: adding graphene powder to anhydrous ethanol at 30°C, stirring at 500rpm for 20min to prepare a graphene ethanol dispersion, wherein the mass volume ratio of the graphene powder to anhydrous ethanol is 0.05:4.0 g / mL; stirring terminal hydroxyl polyamide and zinc dioxide at 500rpm for 10min, and adding them dropwise to the graphene ethanol dispersion, wherein the mass volume ratio of the terminal hydroxyl polyamide, zinc dioxide, and graphene ethanol dispersion is 0.10:0.10 g / mL. :3.0, placing the above mixed solution in an ultrasonic device, and ultrasonically treating it for 25 minutes under the conditions of ultrasonic frequency of 40kHz and ultrasonic power of 300W. After the ultrasonic treatment, continue to stir the mixed solution at 500pm until a sol state is formed, and place the sol in a drying oven and dry it at 80°C for 6h to obtain a gel-like composite; placing the gel-like composite in a sintering furnace, and sintering it at 400°C for 40 minutes under an inert atmosphere; after the sintering, take out the composite and cool it to 30°C, grind it to 50nm, and modify the graphene.
[0026] Example 3
[0027] A high-performance non-stick pan coating includes the following raw materials in parts by weight: 16 parts of bisphenol A epoxy resin, 24 parts of propanol, 9 parts of surfactant, 30 parts of zirconium phosphate layered nanoparticles, 6 parts of nano silicon nitride, 7 parts of nano silicon dioxide, 10 parts of modified graphene, 2 parts of leveling agent, and 2 parts of silane coupling agent. Among them, the surfactant is a combination of polyoxyethylene lauryl ether, dodecyl dimethyl betaine, and dodecyl phosphate potassium salt in a ratio of 1:1:1, the leveling agent is butyl acetate, and the silane coupling agent is a combination of γ-glycidyloxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and vinyltrimethoxysilane in a ratio of 1:1:1. The modified graphene is prepared by the following method: adding graphene powder to anhydrous ethanol at 25°C, stirring at 400rpm for 15min to prepare a graphene ethanol dispersion, wherein the mass volume ratio of the graphene powder to anhydrous ethanol is 0.04:3.50 g / mL; stirring terminal hydroxyl polyamide and zinc dioxide at 400rpm for 7.5min, and adding them dropwise to the graphene ethanol dispersion, wherein the mass volume ratio of the terminal hydroxyl polyamide, zinc dioxide, and graphene ethanol dispersion is 0.07:0.0 g / mL. 7:2.00, placing the above mixed solution in an ultrasonic device, and ultrasonically treating it for 30 minutes under the conditions of ultrasonic frequency of 30kHz and ultrasonic power of 200W. After the ultrasonic treatment, continue to stir the mixed solution at 400pm until a sol state is formed, and place the sol in a drying oven and dry it at 70°C for 8h to obtain a gel-like composite; place the gel-like composite in a sintering furnace, and sinter it at 300°C for 50min under an inert atmosphere; after the sintering, take out the composite and cool it to 25°C, grind it to 40nm, and modify the graphene.
[0028] The high-performance non-stick pan coating described in the above embodiments 1-3 is prepared according to the following process, comprising the following steps:
[0029] (1) adding bisphenol A epoxy resin, surfactant and zirconium phosphate layered nanoparticles into propanol, mixing and stirring at 650 rpm for 35 min under heating condition of 45° C. to prepare a matrix solution;
[0030] (2) adding nano silicon nitride and nano silicon dioxide to the matrix solution, and ultrasonically stirring for 25 min at a stirring power of 300 W and an ultrasonic frequency of 30 kHz to obtain a mixed solution;
[0031] (3) Adding the graphene composite to the mixed solution, stirring at 400 rpm for 17.5 min, then adding a leveling agent and a silane coupling agent, stirring at 400 rpm for 12.5 min, to obtain a high-performance non-stick pan coating.
[0032] Example 4
[0033] Compared with Example 3, the present embodiment is different in that the high-performance non-stick pan coating is prepared according to the following process, including the following steps:
[0034] (1) adding bisphenol A epoxy resin, surfactant and zirconium phosphate layered nanoparticles into propanol, mixing and stirring at 500 rpm for 40 min under heating condition of 40° C. to prepare a matrix solution;
[0035] (2) adding nano silicon nitride and nano silicon dioxide to the matrix solution, and ultrasonically stirring for 30 min at a stirring power of 200 W and an ultrasonic frequency of 20 kHz to obtain a mixed solution;
[0036] (3) Adding the graphene composite to the mixed solution, stirring at 300 rpm for 20 min, then adding a leveling agent and a silane coupling agent, stirring at 300 rpm for 15 min, to obtain a high-performance non-stick pan coating.
[0037] Example 5
[0038] Compared with Example 3, the present embodiment is different in that the high-performance non-stick pan coating is prepared according to the following process, including the following steps:
[0039] (1) adding bisphenol A epoxy resin, surfactant and zirconium phosphate layered nanoparticles into propanol, mixing and stirring at 800 rpm for 30 min under heating condition of 50° C. to prepare a matrix solution;
[0040] (2) adding nano silicon nitride and nano silicon dioxide to the matrix solution, and ultrasonically stirring for 20 min at a stirring power of 400 W and an ultrasonic frequency of 40 kHz to obtain a mixed solution;
[0041] (3) Adding the graphene composite to the mixed solution, stirring at 500 rpm for 15 min, then adding a leveling agent and a silane coupling agent, stirring at 500 rpm for 10 min, to obtain a high-performance non-stick pan coating.
[0042] The high performance non-stick pan coating described in Examples 1-5 above is applied to the inner surface of the pan to obtain a non-stick pan coating.
[0043] Comparative Example 1
[0044] The difference between this comparative example and Example 3 is that the raw material does not contain zirconium phosphate layered nanoparticles.
[0045] Comparative Example 2
[0046] The difference between this comparative example and Example 3 is that the raw material does not contain modified graphene.
[0047] Comparative Example 3
[0048] This comparative example is compared with Example 3, except that an equal weight portion of graphene is used instead of modified graphene.
[0049] Comparative Example 4
[0050] The difference between this comparative example and Example 3 is that no surfactant is added to the raw materials.
[0051] Performance Testing
[0052] The non-stick pan coatings prepared in Examples 1-5 and Comparative Examples 1-4 were subjected to performance tests.
[0053] 1. Alkali resistance test: Refer to the test method and requirements of GB / T 32095.3-2015, pour 2wt% sodium carbonate solution into the non-stick pan to about 2 / 3 of the height, cover and boil, and continue boiling for 10 minutes. Place it at 23℃ for 2 hours, pour out the acetic acid, rinse with clean water and wipe dry with a soft cloth, and check the non-stick surface with a 4x magnifying glass. If there is no bubbling or shedding of the coating, continue the test until the coating does not bubble or shed off, then stop the test. Adding acetic acid once is counted as one cycle, and the previous cycle in which the coating does not bubble or shed off shall prevail. Repeat the test 3 times, and the test results are shown in Table 1.
[0054] 2. Acid resistance test: Refer to the test method and requirements of GB / T 32095.3-2015, pour acetic acid with a concentration of 2wt% into the non-stick pan to about 2 / 3 of the height, cover and boil, and continue boiling for 10 minutes. Place it at 23℃ for 2 hours, then pour out the acetic acid, rinse with clean water and wipe dry with a soft cloth, and use a 4x magnifying glass to check the non-stick surface. If there is no bubbling or shedding of the coating, continue the test until the coating does not bubbling or shedding occurs, then stop the test. Adding acetic acid once is counted as one cycle, and the previous cycle in which the coating does not bubbling or shedding occurs shall prevail. Repeat the test 3 times, and the test results are shown in Table 1.
[0055] 3. Hardness test: Refer to the test method and requirements of GB / T 6739-2022. Use a pencil to scratch the coating surface for 20 mm with a force of 10 N. Gradually increase the hardness of the pencil until visible defects appear on the coating surface. The hardness of the hardest pencil without coating defects is recorded as the coating hardness. Repeat the test 5 times and take the average value and record it in Table 1.
[0056] 4. Adhesion test: Refer to the test method and requirements of GB / T 9286-2021, use a cross-cutting tool to draw 100 lines with an area of 1mm on the coating surface. 2The tip of the cutter must penetrate the coating. Use 3M 600 tape to stick to the cross-cut area, hold one end of the tape, and quickly pull it up at a 90° right angle. Repeat 5 times, using a new tape each time. Observe the shedding of the coating and record the corresponding grade in Table 1. The grade grading standard refers to the requirements of GB / T 9286.
[0057] 5. Life test: Simulate the user's normal use, cook rice with Northeastern rice, cook, keep warm, let the pot cool and clean as one cycle, test for 24 hours without interruption, until the coating starts to fall off in spots, the last cycle when the coating starts to fall off in spots is used as the standard. Repeat the test 3 times, the test results are shown in Table 1.
[0058] Table 1
[0059]
[0060]
[0061] It can be seen from Table 1 that the non-stick pan coatings prepared in Examples 1-5 have high hardness, strong adhesion, good acid resistance, alkali resistance and long service life, especially Example 3 has a better effect.
[0062] By comparing Example 3 with Comparative Example 1, Example 3 is superior to Comparative Example 1 in terms of acid resistance, alkali resistance, hardness, adhesion, and service life. This is because when zirconium phosphate laminar nanoparticles are dispersed in the coating in Example 3, the heat-resistant temperature of the coating and the ability to resist the corrosion of acidic and alkaline chemicals can be effectively improved, and the hardness, wear resistance, and scratch resistance of the coating can also be significantly increased. At the same time, the active site of the zirconium phosphate laminar nanoparticles can form a chemical bond with the functional group in the bisphenol A type epoxy resin molecule, and the epoxy resin molecule is firmly fixed on the surface of the zirconium phosphate laminar nanoparticles. Because the zirconium phosphate laminar nanoparticles have a larger specific surface area and a layered structure, a wide network structure can be formed in the coating, and this network structure closely connects the epoxy resin molecule with nano silicon nitride, nano silicon dioxide, leveling agent, and silane coupling agent to form a more dense network structure, which helps to improve the adhesion and cohesion of the coating, further improve the acid resistance, alkali resistance, and hardness of the coating, and make the coating more firmly attached to the metal substrate, not easy to fall off, and then extend the service life of the coating. In addition, during the curing process of the coating, the zirconium phosphate layered nanoparticles can be peeled off and arranged in a highly ordered manner to form a regular sheet structure. This orderly arrangement not only enhances the physical strength of the coating, but also forms an effective barrier that can greatly slow down or prevent corrosive media such as water, oxygen, acidic or alkaline substances from penetrating into the metal substrate, thereby significantly improving the anti-corrosion performance of the coating and extending the service life of the cookware.
[0063] By comparing Example 3 with Comparative Examples 2 and 3, Example 3 is superior to Comparative Examples 2 and 3 in terms of acid resistance, alkali resistance, hardness, adhesion and service life. This is because in Example 3, graphene is modified by using terminal hydroxyl amide and zinc dioxide. The addition of terminal hydroxyl polyamide makes its amino functional group interact with the graphene surface, and terminal hydroxyl polyamide molecules are grafted in graphene, thereby introducing amino functional groups, significantly enhancing the compatibility of modified graphene with epoxy resin, and improving the adhesion between the coating and the substrate. The amino functional group of the modified graphene reacts with the epoxy group and carboxyl group in the epoxy resin, promoting the cross-linking reaction between the components of the coating, thereby forming a more compact and firm coating structure, reducing the pores and defects in the coating, and then improving the acid resistance, alkali resistance and adhesion of the coating. In the modified sol-gel transition and sintering process, zinc dioxide particles are attached to the graphene surface to form a composite reinforcement structure, which helps to improve the hardness, wear resistance and service life of the modified graphene.
[0064] By comparing Example 3 with Comparative Example 4, the surfactant in Example 3 can be adsorbed on the surface of zirconium phosphate layered nanoparticles, nano silicon nitride, and nano silicon dioxide, and is compatible with the epoxy resin matrix through its lipophilic group, while the hydrophilic group is oriented toward the outside of the particles to form a coating film. This coating film effectively reduces the surface tension between the nanoparticles, prevents the agglomeration of the particles, thereby improving the dispersion of zirconium phosphate layered nanoparticles, nano silicon nitride, and nano silicon dioxide in the epoxy resin and the orientation of zirconium phosphate layered nanoparticles, so that the zirconium phosphate layered nanoparticles can efficiently exert their barrier effect and further improve the corrosion resistance of the coating. At the same time, the nano silicon nitride and nano silicon dioxide are evenly dispersed, so that the overall hardness of the coating is improved, the wear resistance and scratch resistance of the coating are enhanced, and the pores and defects in the coating are reduced, forming a more dense barrier, effectively blocking the penetration of acidic and alkaline substances, thereby significantly improving the acid and alkali resistance of the coating. In addition, surfactants improve the compatibility between the nanoparticles and the epoxy resin matrix, allowing the nanoparticles to bond more firmly to the epoxy resin, helping to improve the adhesion between the coating and the substrate, preventing the coating from falling off or cracking during use, thereby extending its service life.
[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-performance non-stick pan coating, characterized in that: The invention comprises the following raw materials in parts by weight: 10-24 parts of bisphenol A epoxy resin, 12-36 parts of propanol, 6-12 parts of surfactant, 20-40 parts of zirconium phosphate layered nanoparticles, 4-8 parts of nano silicon nitride, 6-8 parts of nano silicon dioxide, 4-16 parts of modified graphene, 1-3 parts of leveling agent and 1-3 parts of silane coupling agent.
2. A high performance non-stick pan coating as claimed in claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 16 parts of bisphenol A epoxy resin, 24 parts of propanol, 9 parts of surfactant, 30 parts of zirconium phosphate layered nanoparticles, 6 parts of nano silicon nitride, 7 parts of nano silicon dioxide, 10 parts of modified graphene, 2 parts of leveling agent and 2 parts of silane coupling agent.
3. A high performance non-stick pan coating as claimed in claim 1, characterized in that: The modified graphene is prepared by the following method: adding graphene powder to anhydrous ethanol at 20-30° C., stirring at 300-500 rpm for 10-20 min, to prepare a graphene ethanol dispersion, wherein the mass volume ratio of the graphene powder to the anhydrous ethanol is (0.03-0.05):(3.0-4.0) g / mL; stirring hydroxyl-terminated polyamide and zinc dioxide at 300-500 rpm for 5-10 min, and adding them dropwise to the graphene ethanol dispersion, wherein the mass volume ratio of the hydroxyl-terminated polyamide, zinc dioxide, and graphene ethanol dispersion is (0.04-0.10):(0.04-0.10) g / mL. :(1.0-3.0), placing the above mixed solution in an ultrasonic device, and ultrasonically treating it for 25-35 minutes under the conditions of ultrasonic frequency of 20-40kHz and ultrasonic power of 100-300W. After the ultrasonic treatment, continue to stir the mixed solution at 300-500rpm until a sol state is formed, and place the sol in a drying oven and dry it at 60-80℃ for 6-10h to obtain a gel-like composite; place the gel-like composite in a sintering furnace, and sinter it at 200-400℃ for 40-60min in an inert atmosphere; after the sintering, take out the composite and cool it to 20-30℃, grind it to 30-50nm, and obtain modified graphene.
4. A high performance non-stick pan coating as claimed in claim 1, characterized in that: The surfactant is one or a combination of polyvinyl alcohol, polyoxyethylene lauryl ether, sodium lauroamphoacetate, dodecyl dimethyl betaine, and potassium dodecyl phosphate.
5. A high performance non-stick pan coating as claimed in claim 1, characterized in that: The leveling agent is one of polydimethylsiloxane, octylphenol polyoxyethylene ether and butyl acetate.
6. A high performance non-stick pan coating as claimed in claim 1, characterized in that: The silane coupling agent is one or a combination of γ-aminopropyl triethoxysilane, γ-glycidoxypropyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, β-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, γ-mercaptopropyl trimethoxysilane and vinyl trimethoxysilane.
7. A process for preparing a high-performance non-stick pan coating as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: (1) adding bisphenol A epoxy resin, surfactant and zirconium phosphate layered nanoparticles into propanol, mixing and stirring under heating conditions of 40-50° C. to prepare a matrix solution; (2) adding nano silicon nitride and nano silicon dioxide to the matrix solution, and stirring uniformly with ultrasonic waves to obtain a mixed solution; (3) Adding modified graphene to the mixed solution and mixing evenly, then adding a leveling agent and a silane coupling agent and mixing evenly to obtain a high-performance non-stick pan coating.
8. The process for preparing a high-performance non-stick pan coating according to claim 7, characterized in that: In the step (1), the stirring speed is 500-800 rpm, and the stirring time is 30-40 min; in the step (2), the ultrasonic stirring power is 200-400 W, the ultrasonic frequency is 20-40 kHz, and the ultrasonic stirring time is 20-30 min; in the step (3), when adding the modified graphene, stirring is performed at 300-500 rpm for 15-20 min, and when adding the leveling agent and the silane coupling agent, stirring is performed at 300-500 rpm for 10-15 min.
9. The process for preparing a high-performance non-stick pan coating according to claim 8, characterized in that: The high-performance non-stick pan coating is applied to the inner surface of the pan.
Citation Information
Patent Citations
Modified zirconium phosphate-epoxy nanometer composite material and preparation method thereof
CN110591294A
Wear-resistant non-stick pan coating and preparation method thereof
CN118291035A
Anticorrosive wear-resistant non-stick pan coating and preparation method thereof
CN118580751A
Cited By
Ceramic non-stick pan coating and application thereof
CN121343452A